2020
DOI: 10.1177/0960327120907131
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-146a inhibits the apoptosis of hippocampal neurons of rats with cerebral hemorrhage by regulating autophagy

Abstract: In this study, to investigate the effect of overexpression of miR-146a on autophagy of hippocampal neurons in rats with intracerebral hemorrhage (ICH), 72 Sprague-Dawley rats were randomly divided into the sham, ICH, miR-146a agomir, and miR-146a agomir control groups. The ICH model was constructed by injection of collagenase VII. The apoptosis of hippocampal neurons was measured by TUNEL assay. The levels of LC3 and Beclin 1 were analyzed by immunohistochemistry. Mitochondrial autophagy was examined by transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Although the regions of hippocampus and cortex are not in situ hemorrhagic foci, ICH can lead to secondary nerve injury, including neuronal death and apoptosis in the hippocampus and cortex (5,34). In the present study, ICH rats exhibited cognitive decline, and the hippocampus and cortex presented neuronal death and apoptosis-related changes, consistent with previous studies (35,36). The mechanisms of brain injury after ICH include not only the initial mechanical injury induced by the hematoma mass effect, but also subsequent damage called SBI (1).…”
Section: Discussionsupporting
confidence: 92%
“…Although the regions of hippocampus and cortex are not in situ hemorrhagic foci, ICH can lead to secondary nerve injury, including neuronal death and apoptosis in the hippocampus and cortex (5,34). In the present study, ICH rats exhibited cognitive decline, and the hippocampus and cortex presented neuronal death and apoptosis-related changes, consistent with previous studies (35,36). The mechanisms of brain injury after ICH include not only the initial mechanical injury induced by the hematoma mass effect, but also subsequent damage called SBI (1).…”
Section: Discussionsupporting
confidence: 92%
“…miR-146a is a single-stranded noncoding small RNA that regulates gene expression by binding to target mRNAs. As an important innate immune signal regulator, miR-146a is involved in the immune response process of various autoimmune and infectious diseases [ 14 ]. Exosomes are nanoscale particles that can effectively deliver miRNA to recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…The result further indicated that miR-146a overexpression corrected inflammation and edema in ALI mice. Evidences exhibit that overexpression of miR-146a inhibits the apoptosis in rat hippocampal neurons [27] and in primary human retinal microvascular endothelial cells [28]. However, few studies suggested miR-146a induced apoptosis in neuroblastoma cells and inhibited proliferation [29] and induced apoptosis in osteoblast [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%